Cantonese amahs’ ‘Public House’: A model of Chinese women immigrants’ voluntary association / Loh Sub Mui - Loh , Sub Mui (1985)
Cantonese unattached female workers who emigrated to Malaya from China between 1933-1938 were of two kinds. Firstly, there were widows and wives forced into separation from their husbands because of economic or social circumstances and had to make their own decisions about their future. Secondly there were spinsters who had taken vows not to marry when still in China and wives who were ritually married but where marriage was not consummated. Such women were associated in their homeland with a female anti-marriage movement originating something in the late 19th century in the Kwangtung district of Shun-te. With them they brought some cultural instittutions and practices which were popular as anti-marriage societies in Kwangtung. These institutions and practices which served their many social needs was successfully practised in a foreign coutry owing to tis adaptability to new environment. Among these, is a unique form of voluntary association called the ‘public houses’ i.e the ‘kung sz uk’ and ‘tsz mooi uk’. The picture given in this study may not be representative of the amahs in general. Statistical accurancy cannot be claimed in regard to the figures that have been given nor can the complete exactitude of all information be guranteed. This is regretable but inevitbale since the amahs themselves seemed not to have a full knowledge of their own customs and there are certain customs which they are practising just because others have been practising them. However, this is an attempts to present the facts in an objective and descriptive manner.